2023
DOI: 10.3390/v15020493
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Cardiovascular Sequelae after SARS-CoV-2 Infection: A Narrative Review Focusing on Athletes

Abstract: Cardiovascular (CV) involvement after severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) infection was found to be frequent among the general population, especially in the pre-vaccination era, and particularly for hospitalized patients or those who experienced a more severe course of the disease. The spectrum of CV disease varies; however, acute myocarditis is particularly fearsome for the athletic population due to the possible associated risk of malignant arrhythmias during training. Alarming percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…Prolonged QTc and QTd due to ventricular repolarization abnormalities are risk factors that can enhance the likelihood of malignant arrhythmia. 32 In addition to these characteristics, we demonstrated that an increased frontal QRS-T angle could be an independent measure of disease severity. In our study, the difference in ECG (QTc, frontal QRS-T angle) between patients in the intensive care unit and those receiving the COVID-19 service suggests that the virus may impact ventricular depolarization and ventricular repolarization.…”
Section: Discussionmentioning
confidence: 72%
“…Prolonged QTc and QTd due to ventricular repolarization abnormalities are risk factors that can enhance the likelihood of malignant arrhythmia. 32 In addition to these characteristics, we demonstrated that an increased frontal QRS-T angle could be an independent measure of disease severity. In our study, the difference in ECG (QTc, frontal QRS-T angle) between patients in the intensive care unit and those receiving the COVID-19 service suggests that the virus may impact ventricular depolarization and ventricular repolarization.…”
Section: Discussionmentioning
confidence: 72%